Moderate intensity aerobic exercise training reduces total and regional diaphragm hyperemia during submaximal exercise in pulmonary hypertensive rats - Kenney, Nathan J. (My University, 2026)
Introduction: Pulmonary hypertension (PH) is a cardiopulmonary disease characterized by vascular remodeling of the pulmonary arteries, increased respiratory muscle work, dyspnea, and reduced maximal oxygen uptake (V̇O₂max). Previous findings from our lab revealed that, specifically, diaphragm blood flow (Q̇) is increased at the expense of hindlimb muscle Q̇ during submaximal treadmill exercise in PH, like that seen in chronic heart failure. Exercise training has been demonstrated to improve V̇O₂max, augment muscle Q̇, and reduce the "respiratory muscle blood flow steal" phenomenon in heart failure; therefore, in this study, we examined whether moderate-intensity aerobic exercise training would have the same effects in PH. We hypothesized that 4 weeks of exercise training would: 1. Increase V̇O₂max and exercise tolerance in PH rats towards that of healthy rats. 2. During moderate/heavy exercise, reduce respiratory muscle (diaphragm, intercostal) blood flow "steal" and increase hindlimb muscle Q̇ and reduce blood [lactate]. Methods: Female Sprague-Dawley rats were randomized into 3 groups: healthy control (HC; n=12), sedentary PH (PH-SED; n=14), and exercise-trained PH (PH-ExT; n=13). All PH rats received a single dose of monocrotaline (MCT; 50mg/kg, i.p.), whilst HC rats received saline vehicle. Echocardiography was used to monitor disease progression (i.e., peak pulmonary arterial acceleration time/ejection time [PA AT/ET]). All rats were acclimated to treadmill running for 5 days before PH-ExT rats performed 4 weeks of moderate-intensity treadmill running (25m/min, 15 min day one, increased by 5 min/day to 60 min). Upon confirmation of PH (AT/ET <0.30), V̇O₂max testing was performed to assess exercise capacity and tolerance. ~24 hours later, respiratory and hindlimb muscle blood flows (Q̇) were determined by infusing fluorescent microspheres at rest and during moderate/heavy-intensity exercise (25m/min). Rest and exercise arterial blood gases, acid-base, and [lactate] were also measured. Results: All PH rats displayed morphometric and echocardiographic criteria for PH, including elevated right ventricular (RV) systolic pressure, RV hypertrophy (RV/LV+S), and reduced PA AT/ET vs. HC (P < 0.05). Exercise training did not increase V̇O₂max in PH-ExT to that of HC rats (64.9 ± 6.5 vs. 75.4 ± 8.4 ml/kg/min; P < 0.001). However, PH-EXT achieved a greater speed during V̇O₂max testing than PH-SED (51.4 ± 4.1 vs. 44.6 ± 2.6 m/min; P < 0.001), which was not different from HC (49.9 ± 3.7 m/min; P = 0.59) and a greater tolerable duration of exercise compared to PH-SED (392 ± 50) vs. 268 ± 54 s.; P < 0.001) and HC rats (331 ± 55 s.; P = 0.017). At rest, total and regional diaphragm Q̇ were not different among groups (P > 0.121; all groups). However, during exercise, PH-ExT rats had a lower total diaphragm Q̇ compared to PH-SED (290 ± 103 vs. 367 ± 149 ml/min/100g; P = 0.036), but this was not different from HC (266 ± 68 ml/min/100g: P = 0.266). Also, exercising PH-ExT rats displayed a decreased ventral costal (210 ± 63 vs. 304 ± 211 ml/min/100g; P = 0.05) medial costal (340 ± 105 vs. 434 ± 235 ml/min/100g; P = 0.030), crural (227 ± 55 vs. 474 ± 404 ml/min/100g; P = 0.006), and intercostal (45 ± 18 vs. 72 ± 27 ml/min/100g; P = 0.011) Q̇ compared to PH-SED. Exercising blood [lactate] was 47% lower in PH-ExT versus PH rats (3.2 ± 2.5 vs. 6.0 ± 2.3 mmol; P < 0.001). During exercise, PH-ExT rats had lower white gastrocnemius Q̇ versus PH-SED (32 ± 21 vs. 54 ± 42 ml/min/100g; P = 0.050) and HC (55 ± 27 ml/min/100g; P = 0.027). Conclusions: Although this moderate-intensity exercise training program did not improve V̇O2max in this preclinical model of PH, it improved exercise tolerance and economy and reduced exercising blood lactate. Decreases in total and regional diaphragm and accessory respiratory muscle Q̇ support that training decreased the work of breathing in PH. Thus, exercise training can promote cardiorespiratory and muscular adaptations that may help alleviate the burden of PH and potentially increase quality of life.
Keywords: Pulmonary hypertension; Exercise training; Animal model